Detection and isolation of plant‐associated bacteria scavenging atmospheric molecular hydrogen. (21st January 2016) - Kanno, Manabu; Constant, Philippe; Tamaki, Hideyuki; Kamagata, Yoichi
Summary: High‐affinity hydrogen (H2 )‐oxidizing bacteria possessing group 5 [NiFe]‐hydrogenase genes are important contributors to atmospheric H2 uptake in soil environments. Although previous studies reported the occurrence of a significant H2 uptake activity in vegetation, there has been no report on the identification and diversity of the responsible microorganisms. Here, we show the existence of plant‐associated bacteria with the ability to consume atmospheric H2 that may be a potential energy source required for their persistence in plants. Detection of the gene hhyL   – encoding the large subunit of group 5 [NiFe]‐hydrogenase – in plant tissues showed that plant‐associated high‐affinity H2 ‐oxidizing bacteria are widely distributed in herbaceous plants. Among a collection of 145 endophytic isolates, seven S treptomyces strains were shown to possess hhyL gene and exhibit high‐ or intermediate‐affinity H2 uptake activity. Inoculation of A rabidopsis thaliana (thale cress) and O ryza sativa (rice) seedlings with selected isolates resulted in an internalization of the bacteria in plant tissues. H2 uptake activity per bacterial cells was comparable between plant and soil, demonstrating that both environments are favourable for the H2 uptake activity of streptomycetes. This study first demonstrated the occurrence of plant‐associated high‐affinity H2 ‐oxidizing bacteria and proposed their potential contribution as atmospheric H2 sink.